(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Posterior reversible encephalopathy syndrome (PRES) is a recently described clinicoradiologic entity that is associated with several medical conditions like hypertensive encephalopathy and eclampsia. It present with headache, confusion, visual disturbances or blindness, and seizures. Parieto-occipital white matter changes due to vasogenic edema can be observed on imaging modalities. It rarely occurs without seizures. There have been reports about PRES associated with pregnancy, especially peripartum. It is often, but not always, associated with high blood pressure. The pathophysiology of PRES is not still clear. Here we report a 23-yearold primigravida with unremarkable antenatal period but complicated by PRES with seizures at her 5th postpartum day. Postictal findings reported headache and magnetic resonance imaging (MRI) findings suggested that PRES were evident. Clinical improvement with complete resolution without any complications was observed on the 8th post operative day with supportive treatment. This case report highlights the importance of awareness, prompt diagnosis and treatment to improve the outcome in this potentially life-threatening, but reversible condition. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 46-49